What's in a word: the use, misuse, and abuse of the word “persistence” in Chlamydia biology - Bavoil, Patrik M. (Frontiers in Cellular and Infection Microbiology, 2014)
The word persistence was used by Chlamydia researchers almost as soon as Chlamydia research was born to reflect the propensity of chlamydiae to cause inapparent infection in their hosts, from birds to humans. More recently, the term persistence has been used, misused, and sometimes abused amidst in vitro and in vivo studies that aim to mimick the ability of chlamydiae to emerge from the presumed inapparent state into clinically detectable infection and disease. Here, I have attempted to provide a global perspective on the state of research on chlamydial persistence, revisiting old observations that may warrant a new look, critically evaluating more recent observations and their shortcomings, and including recent developments that may help redefine chlamydiae as pathogens—or not—of both animals and humans.